A retrospective exploration of formal and social support received: experiences of secondary victims of homicide in England and Australia - O'Neill, Ann Margaret (Curtin University, 2010)
This qualitative retrospective descriptive study explored English and Australian secondary victims of homicidenarrativesof their experiences in order to identify and delineate their post homicide support needs. This thesis is a study of the experiences of support proffered to secondary victims of homicide in England and Australia, and their perceptions of the nature of that support. The support included, but was not limited to, support needs emanating from within the criminal justice system.The study also documented the support secondary victims of homicide experienced in totality in order to develop an evidence base from which to better understand the sources of support available to the victims. Underpinned by a range of social theories including the World Health Organisation’s (WHO) health construct, Maslow’s Hierarchy of Needs, and contemporary grief, trauma, and victimology theories, this descriptive study relied on constant comparisons to analyse the content of 28 face-toface semi-structured interviews.A systematic in-depth review of data revealed that the relative rate at which people affected by homicide discussed helpful support, be it from their existing social support network or beyond their formal support network, was almost equal, and the majority of all support was described as helpful. However, analysis at the intermediate and personal level (meso and micro levels) identified some support sources were reported as being significantly more helpful than others.The results documented the demographic profile of the secondary victims of homicide, the circumstances surrounding their experiences of homicide and the sources of support they identified, the number of times each was mentioned and the nature of the support experience described i.e. how effective the support experienced was based on if it was described as helpful or unhelpful. The specific supportive relationships identified were grouped into sources, systems, and networks.Four themes emerged from the study that suggest that people in supportive roles must be mindful that homicide experiences are complex and elongated, random acts of kindness are profoundly helpful, family and friends feature strongly in discussions of support, and any support must be provided in a holistic manner.Analysis of the data at the network level (the macro level) revealed that the formal and social support networks featured strongly. However, further scrutiny revealed support provided by the social support network was described as unhelpful in significantly less instances than that provided by the formal support network. Analysis of support systems data (the meso level) revealed that support provided by friends, community and family was consistently referred to as helpful, whereas support provided by therapeutic, justice and public support systems was regularly described as unhelpful.Examination of the data in relation to each of the identified sources of support revealed that those most helpful for secondary victims of homicide were educational facilities, other victims of the offender, generic grief support, children and work places. Support from the forensic mental health services, the offender, the associates of the offender, organisations, post court services, and generic therapeutic services were commonly described as unhelpful. The findings also documented that secondary victims of homicide experience an array of supportive experiences over many years whilst dealing with a multitude of personal, emotional, and psychosocial stressors that arise out of their unique and complex circumstances and experiences of victimisation.The results of this research conclude that the established presence of high levels of trauma and complicated grief in this population may make them more vulnerable to subsequent experiences of trauma and injustice, accounting for why unhelpful experiences of support (secondary victimisations) described in this study were particularly harmful, despite the overall relatively high prevalence of helpful experiences of support. This study also deconstructed the concept of ‘support’ for secondary victims of homicide, identifying nine support systems, which involved a range of 35 support sources available to secondary victims of homicide. Having identified these support systems and sources, this study went on to explore the helpfulness of these supports to secondary victims of homicide.Finally, a model is proposed to identify, and delineate three dynamic dimensions of post homicide support, the buffering factors (needs), structural supports available (resources), and the type and nature of support provided (functions). Suggestions put forward by the participants are presented and several recommendations are proposed on to how to better support secondary victims of homicide.